(3eONd Edi GdEbJUGO GdLRFj (B/s - (3Jdhf, aQOQjcs; (3hGTO, hQOjIs ((3HjQhJ(B: s (3eLO GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ(B, s, 2008)
(3GdHMK Yf GdJhGRf GdWdH,GdYQV hGdShb,JMbjb GdMO GdCbUi ef GdeJYI Sdhc GdeSJgdc,Ndb KQhGJ LOjOI GdEfJGL hGdJcGdja,GdUQGY ef CLd GdCShGb GdefJL aj hVY efGaSI,bOQI GdeDSSI GdcHjQI GdEMJcGQ,ef GdJgOjO Edi GdJhGWD GMJcGQ GdbdI,GdCLQ,GdEjQGO hGdaGFOI Jchjf SYQ GdYhGed,ehGLgI dYLR GdShb JONd GdOhdI,GdehGRfI Hjf GdMGVQ hGdeSJbHd GdNjGQGJ eG Hjf GdCReIs
(3GdedGMb(B:(3U U(B.289-294 (3HHdjhZQGajG(B:(3U U(B.295-296s
Keywords: (3GdGbJUGO GdLRFjs